Analisis Yuridis Atas Peralihan Hak Atas Tanah yang Tidak Dilakukan Dihadapan Ppat (Pejabat Pembuat Akta Tanah) (Studi Pada Perumahan Bumi Berngam Baru Di Kota Binjai) - Siti Melisa Harahap (Universitas Harapan Medan, 2021)
Land title transfer is the transfer of land rights from the old owner to the new one. According to the adat law, land title transfer is a clear and cash transaction. What it means by ‘clear’ is that the transfer has to done before an Adat leader or a PPAT (official empowered to draw up land deeds), and what it means by ‘cash’ is that the title transfer and the payment have to be done simultaneously. In reality, however, many land title transfers are not done before PPATs. The research problems are how about the regulation on land title transfer according to laws, how about the process of transfer which is not done before a PPAT, ad how about the legal consequence of land title transfer which is not done before a PPAT. The research used juridical normative method with descriptive design. It also used juridical empirical method by conducting interviews as primary data and library research as secondary data. The gathered data were analyzed qualitatively in orderto answer the research problems. Land title transfer is specified in Articles 1457 and 1458 of the Civil Code, in the Adat law on clear and cash, and in the Land Act based on the adat law. The process of land title transfer which is not done before a PPAT violates Article 37 of PP No. 24/1997 on Land Registration as what has occurred at PerumahanBumiBerngam, Binjai, but the Purchase contract can be used as the process of transfer title, and when it is done underhandedly, let alone when it is identified with only a piece of receipt, it cannot give legal certainty and legal protection for the buyer. Legal consequence of land title transfer which is not done before a PPAT will not have anylegal certainty.